Ekstraksi limonit dengan metode dua tahap reduksi selektif dan magnetic separation dengan variasi waktu tahan dan suhu rendah - Budiyanto, Eko; Yuono, Lukito Dwi; Bahfie, Fathan; Sulistiyo, Danang (TURBO [Tulisan Riset Berbasis Online], 2021)
The use of limonite and saprolite nickel ore with low Ni content as raw material for the manufacture of FeNi metal with a content of> 5% Ni has not been widely used. This is because to process limonite and saprolite ore into high levels of FeNi concentrate, it requires greater energy. The purpose of this study was to see the beneficiation process of low grade laterite nickel ore (limonite type, with 1-2% Ni content) at low temperature and holding time with graphite reducing agents and adding additives to iron nickel concentrate and nickel iron concentrates with nickel content above 5%. The method used in this research is to provide services with temperature variations of 250°C, 300°C, and 350°C with a holding time of 60 minutes and 90 minutes in the heat process stage 1 and continued in the heat process stage 2, namely at a temperature of 1150°C with a holding time of 60 minutes. The concentrates and tailings resulted from magnetic separation were then subjected to XRF testing and optical microscopy. With the erasing process and the holding time, the nickel content was quite high, namely 5-6%. With this, it can be neglected that the beneficiation process with this method is very effective and optimal. The levels of Fe in the concentrate obtained from several tests have increased and decreased with the addition of temperature and holding time.